Metaphysical basis of sociological recognition (Journal of Philosophy Culture and Political Science, 2018)
Starting an analysis of metaphysical groundssocial knowledge is necessary to decide oncategorical apparatus, having considered ininterconnection, first of all the category of generaland history.By the middle of the 19th century, finally formedthe question of what constitutessocial life and what is its nature ifdetermine the latter without going beyondmost public life and historicalreality. All this lets talk aboutshaping sociology as a process ofdevelopmentally related to the whole complexco-humanities disciplines.